Communication-aware virtual machine migration in cloud data centres. (2017) - Xue, Weilian; Li, Wenxin; Qi, Heng; Li, Keqiu; Tao, Xiaoyi; Ji, Xinhua
The virtual machine (VM) migration technology is widely used in cloud data centres for achieving load balance, or saving energy consumption. Despite the potential benefits of the VM migrations, relatively little work has taken the inter-VM communication into account, with researchers mainly focusing on reducing the network cost of migration or the energy cost. In this paper, we focus on the VM migration problem in the context of large volume of inter-VM communication traffic. To this end, we make decisions on three problems of when, which, and to where the VMs shall be migrated. Specifically, we formulate an optimisation of minimising the number of migrations as well as the cost of both inter-VM traffic and migration traffic. To solve the optimisation, we design an efficient communication-aware VM migration algorithm and seamlessly combine three types of resources: CPU, memory and bandwidth. Finally, we conduct comprehensive experiments based on the CloudSim simulator. Extensive simulation results show that the proposed method can outperform the state-of-art RIAL and Sandpiper, in terms of the following three metrics: the number of migrations, the inter-VM communication cost, and the migration network cost.